Prenatal study on ossification and growth of long bones in sheep foetus - Nissar, Shazia; Basha, Sabiha Hayath; Ramesh, Geetha; Mayakkannan, Thippan; Vimal, R. (Indian Journal of Veterinary Anatomy, 2018)
The present was conducted on twenty four sheep embryo and foetus ranging from 30 to 90 days of gestation. The study included appearances of ossification centers in forelimb and hind limb by using double staining method. The primary ossification center in different age groups 45, 52, 66 and 82 days. The total length (TL), ossified length (OL),ossified width (OW) of bones was studied. Total length (TL), ossified length (OL) and ossified width (OW) of forelimb and hind limb of different age of embryo and foetus showed significant difference.